PENGARUH TURUNNYA HARGA LADA TERHADAP PEREKONOMIAN MASYARAKAT DESA BENCAH BANGKA BELITUNG - Maharani, Aprilia; Sumiyanti, Sumiyanti (Ekonomi & Bisnis, 2019)
This study is a case study of the influence of the decline in pepper prices on the economy of the people of Bencah Village, Bangka Belitung Islands. The research was conducted aimed at finding out how much the impact of the current decline in pepper prices on the income of the people in the study location. Where this research was carried out in Bencah Village,Air Gegas District,South Bangka Regency,Bangka Belitng Islands. By using primary and secondary data. Primary data is done through questionnaire distribution techniques with the number of respondents as many as 35 people selected from the farmers, entrepreneurs, civil servants and honorariums as well as secondary data through a study of related party reports and documents that have a correlation and relevance to this study.Then analyzed by descriptive and qualitative approaches, namely through the presentation and preparation of data in the form of percentages. The results of the study and discussion found that 94.6% of the village community felt that the decline in pepper prices had an impact on their income. The range of decreases in income perceived by farmer groups is 70% -100%, income entrepreneurs are decreasing in the range of 40% -70%,while for people who work as civil servants and honerers their income declines range from 20% -40% .The solution given by the government regarding the problems in this study is the pepper warehouse receipt prpgram which is currently not realized at the research location.